Development of Platformer Game “Adventure Drake” Using Finite State Machine Method - Roby Setiawan; Agus Nugroho; Redhy Putra, Bima (MASE - Media Applied and Engineering, 2024)
Video game is one of the most popular hobbies out there, someone who have been played games always ended with fun experience and adrenaline rush. The people who enjoy this type of hobby so diverse starring with kids, teenager, and adult. With increasing technology playing game is not exclusive on desktop pc or game console, but now can be play on smartphone with android and IOS system operations, so they can play game wherever they want, and whenever they want. For that reason, the author with interested in designing game with the platformer genre using 2D technology and using finite state machine for controlling character animation Therefore author make research platformer game adventure drake using finite state machine, the itself game can be played by anytime at anywhere. The main reason to building this game therefore adding onto the collection Indonesia game’s and analyses the game with implementing finite state machine method. The result from building this game is great, the game success implementing both 2D technology and finite state machine.